2021
DOI: 10.3389/fcell.2021.636765
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Porcine Immature Oocyte Vitrification on Actin Microfilament Distribution and Chromatin Integrity During Early Embryo Development in vitro

Abstract: Vitrification is mainly used to cryopreserve female gametes. This technique allows maintaining cell viability, functionality, and developmental potential at low temperatures into liquid nitrogen at −196°C. For this, the addition of cryoprotectant agents, which are substances that provide cell protection during cooling and warming, is required. However, they have been reported to be toxic, reducing oocyte viability, maturation, fertilization, and embryo development, possibly by altering cell cytoskeleton struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…To date, vitrification is the most efficient and widely used method in pig embryo cryopreservation, particularly the ultra–rapid vitrification systems [ 11 , 25 29 ]. Vitrification has been successfully used on embryos at early stages of development [ 14 , 30 ] and also on oocytes [ 20 , 31 , 32 ]. However, the lower pregnancy rates achieved for vitrified embryos (ranging from 39% to 75%) when compared to fresh ones [ 24 , 33 ], the need of highly qualified personnel for vitrification and surgical embryo transfer to achieve high pregnancy and prolificacy rates, represent major hurdles for pig embryo cryopreservation.…”
Section: Introductionmentioning
confidence: 99%
“…To date, vitrification is the most efficient and widely used method in pig embryo cryopreservation, particularly the ultra–rapid vitrification systems [ 11 , 25 29 ]. Vitrification has been successfully used on embryos at early stages of development [ 14 , 30 ] and also on oocytes [ 20 , 31 , 32 ]. However, the lower pregnancy rates achieved for vitrified embryos (ranging from 39% to 75%) when compared to fresh ones [ 24 , 33 ], the need of highly qualified personnel for vitrification and surgical embryo transfer to achieve high pregnancy and prolificacy rates, represent major hurdles for pig embryo cryopreservation.…”
Section: Introductionmentioning
confidence: 99%
“…Modifications of vitrification devices, the type of cryoprotectant and the procedure used were tested, aiming at reducing cryoinjuries and cellular changes of the vitrified-warmed oocytes. Notably, vitrification induces several changes within porcine oocytes, such as in the cytoskeleton [100], mitochondrial abnormalities [101], epigenetic changes [102] and decreased expression level of the Type 1 inositol 1,4,5 trisphosphate receptor [103]. More recently, vitrification of porcine oocytes has been associated with alterations at transcriptomic and proteomic levels [37,104].…”
Section: Pigmentioning
confidence: 99%
“…Vitrification is an ultrafast cooling method performed with a very high concentration cryoprotectant for dehydration to avoid the formation of ice crystals during oocyte cryopreservation, which ultimately leads to higher cell survival, fertilization, embryo development and pregnancy rates compared with traditional slow-freezing [3][4][5][6]. However, studies reveal that impaired oolemma permeability [5], oxidative stress [7] and the toxicity of cryoprotectants during vitrification [8] can still cause damages to the oocytes [9,10], especially deteriorating cytoskeleton [11] and mitochondrial function [12,13], which eventually obstruct subsequent embryo development and need further study [14][15][16]. It is reported that mechanical properties play a pivotal role in oocyte development [17].…”
Section: Introductionmentioning
confidence: 99%